Pengaruh konseling laktasi intensif terhadap pemberian air susu ibu (ASI) eksklusif sampai 3 bulan - Ambarwati, Ria; Muis, Siti Fatimah; Susanti, Purwanti (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2013)
Background : In 2010 within the area of Semarang Municipality, exclusive breastfeeding by mothers to their babies reaches up to only 20,06%. One of the problems was the lack of lactation counseling especially by the health service institutions. Objectives: To reveal the effect of intensive lactation counseling on exclusive breastfeeding up to 3 months. Method: This research study was designed as a quasi-experiment of non-equivalent control group. The population of this study was a group of mothers who were in the 7th to 8th months of pregnancy bearing the second child or more. The number of the subjects was 25 mothers who were grouped into 2: the experimental groups of 12(n=12) and 27 control group of 13 (n=13). The group underwent a treatment of intensive lactation counseling of 9 times on 2 stages, the first was four-time treatments during the medical examination on their pregnancy of 7th – 8th months. The second stage of treatments was done by home visit for 5 times during week 1, 2, 4, 8, and 12 after giving birth by certified lactation counselors for 40 work hours. These counselors had the experience of at least 5 clients counseling. The control group had the usual counseling that they normally received from the midwives at the Health Primary Center and private midwives nearby. Results: The group without intensive lactation counseling showed no gain of knowledge, attitude towards early initiation of breastfeeding, exclusive breastfeeding, breastmilk and no increase of the number of exclusive breastfeeding on their babies prior to and during the study. The group with intensive lactation breastfeeding shows a significant gain of knowledge, positive attitude towards early initiation of breastfeeding, exclusive breastfeeding, breastmilk and significant increase of the number of exclusive breastfeeding for 3 months on their babies that born prior to and during the study from 2(16,7%) to 10(83,3%). Conclusion: Intensive lactation counseling increases the practice of exclusive breastfeeding up to 3 months. Keywords : intensive lactation counseling, exclusive lactation breastfeeding, 3 months